ANAKRONISME DALAM CERITA RAKYAT KABUPATEN INDRAGIRI HULU - Sania, Dwi Rara Sania Rara; Rahman, Elmustian Rahman; Rumadi, Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : This research gets art criticism basis. About problem which is worked through which is anachronism in Regency folkloric bulk Indragiri Hulu. Pengkajian on elemental anachronism constitutes one study which absorbing. One folklore which relates about a sukar's scene escaped from by anachronism. That anachronism is alone constitute picture or reputed painting unlike reality. In anachronism exists incompatibility thing something with: given epoch unsuitably terminologicals time, figure place unsuitably terminologicals time, scene kepts the ball rolling unsuitably terminological time, latar's age unsuitably terminologicals time, and irrational something (incredible something) in art opus. About problem which interests analisis's writer which is how forms anachronism in Regency folkloric bulk Indragiri Hulu who gets bearing with irrational something, by use of descriptive method. Data source on observational it which is Regency folklore bulk Indragiri Hulu that acquired of many title binds books which is Cerita Rakyat Indragiri Hulu one that published by Zoom Local Government II. Inhu Year 1997, Cerita Rakyat dari Riau B.M opus. Syamsuddin, Kerajaan Indragiri Hasan Junus Dkk's opus , Cerita Rakyat Indragiri Hulu Mahligai Keloyang dan Sejumlah Cerita Lainnya karya Drs. Elmustian Rahman, MA dan Drs. Fakhri, and Kumpulan Cerita Rakyat INHU (Indragiri Hulu) yang diterbitkan oleh Dinas Pendidikan Kabupaten Indragiri Hulu tahun 2001. This observational data as sentence that load anachronism that exists in Regency folkloric bulk Indargiri Hulu. Data collecting did by bibliography tech, tech reads, and tech notes. That data then dianalisis passes through analisis's tech descriptive kualitatif which is each sentence that load found anachronism deep Regency folkloric bulk Inhu at indication and strengthened by prove. This observational result exists 44 sentence that contain anachronism of 21 Indragiri Hulu's Regency folklores. Keyword: anachronism, foklore, Indragiri Hulu